Inequality in health: socioeconomic differentials in mortality in Rome, 1990-95. Issue 11 (1st November 1999) - Michelozzi, P; Perucci, C A; Forastiere, F; Fusco, D; Ancona, C; Dell'Orco, V
Abstract : STUDY OBJECTIVE: Population groups with a lower socioeconomic status (SES) have a greater risk of disease and mortality. The aim of this study was to investigate the relation between SES and mortality in the metropolitan area of Rome during the six year period 1990-1995, and to examine variations in mortality differentials between 1990-92 and 1993-95. DESIGN: Rome has a population of approximately 2, 800, 000, with 6100 census tracts (CTs). During the study period, 149, 002 deaths occurred among residents. The cause-specific mortality rates were compared among four socioeconomic categories defined by a socioeconomic index, derived from characteristics of the CT of residence. MAIN RESULTS: Among men, total mortality and mortality for the major causes of death showed an inverse association with SES. Among 15-44 year old men, the strong positive association between total mortality and low SES was attributable to AIDS and overdose mortality. Among women, a positive association with lower SES was observed for stomach cancer, uterus cancer and cardiovascular disease, whereas mortality for lung and breast cancers was higher in the groups with higher SES. Comparing the periods 1990-92 and 1993-95, differences in total mortality between socioeconomic groups widened in both sexes. Increasing differences were observed for tuberculosis and lung cancer among men, and for uterus cancer, traffic accidents, and overdose mortality among women. CONCLUSIONS: The use of an area-based indicator of SES limits the interpretations of the findings. However, despite the possible limitations, these results suggest that social class differences in mortality in Rome are increasing. Time changes in lifestyle and in the prevalence of risk behaviours may produce differences in disease incidence. Moreover, inequalities in the access to medical care and in the quality of care may contribute to an increasing differentials in mortality.